Innovation in agribusiness: a study of key trends, actors and impacts in the scientific literature (2014-2024) - Forno, Natália Sartori Dal; Rosa, Carmen Brum; Venturini, Simone; Rech, Charles (Brazilian Journal of Production Engineering, 2025)
The agribusiness sector is a pillar of the Brazilian economy, contributing significantly to the country's economic growth. In a sector characterized by constant evolution, innovation is fundamental to guarantee positive results and drive new achievements in the global market. Motivated by this premise, the present study aims to analyze, through a review of the existing literature, the main publications related to innovation in agribusiness. The systematic review follows five phases: definition of research question, selection of database, definition of search methodology, research and tabulation of relevant studies, highlighting of results and study presentation. The VOSViewer® software verifies the links between the researched documents and authors. The analysis identifies the trends and innovative practices in agribusiness and the role of different agents in the innovation process. The results offer valuable insights on innovation in agribusiness, which encompasses several areas, from the adoption of digital technologies and precision agriculture to the development of new business models. The collaboration between different actors, such as companies, universities, governments and rural producers, is essential to drive innovation and ensure its effective adoption in the field.
Keywords: innovation; agribusiness; systematic review